IMPLEMENTASI BUKU PENDIDIKAN PANCASILA BERBASIS ISU PERUBAHAN IKLIM UNTUK MENINGKATKAN KEPEDULIAN LINGKUNGAN SISWA SD - Khomariyah, Lailatul; Riefa'ah, Lailiatur; Rohmah, Sailir; Rahmawati, Sri; Mujtahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aims to foster environmental awareness among fourth-grade students through the use of a Pancasila Education textbook that integrates climate change issues. The study was conducted at SDN Dlemer 1 using the Kemmis and McTaggart model, which consists of the planning, implementation, observation, and reflection stages carried out over two cycles. The research subjects consisted of 32 fourth-grade students. Data collection techniques were conducted through observation and interviews, while data analysis used simple qualitative and quantitative descriptive analysis. The results of the study indicate that the use of the Pancasila Education textbook integrated with climate change issues is effective in enhancing students’ environmentally conscious character. This improvement is evident in the percentage of students meeting the indicators of environmentally conscious character, rising from 56% in the pre-cycle phase to 72% in Cycle I and further increasing to 88% in Cycle II. Students also demonstrated positive behavioral changes, such as disposing of trash properly, conserving electricity, maintaining classroom cleanliness, and actively participating in environmental care activities. Thus, the use of Pancasila Education textbooks integrated with climate change issues can serve as an effective learning alternative to strengthen the environmentally conscious character of elementary school students.